Seasonal training-load quantification in elite English Premier League soccer players - Malone, J. J.; Di Michele, R.; Morgans, R.; Burgess, D.; Morton, J. P.; Drust, B. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To quantify the seasonal training load completed by professional soccer players of the English Premier League. Methods: Thirty players were sampled (using GPS, heart rate, and rating of perceived exertion [RPE]) during the daily training sessions of the 2011-12 preseason and in-season period. Preseason data were analyzed across 6 × 1-wk microcycles. In-season data were analyzed across 6 × 6-wk mesocycle blocks and 3 × 1-wk microcycles at start, midpoint, and end-time points. Data were also analyzed with respect to number of days before a match. Results: Typical daily training load (ie, total distance, high-speed distance, percent maximal heart rate [%HRmax], RPE load) did not differ during each week of the preseason phase. However, daily total distance covered was 1304 (95% CI 434-2174) m greater in the 1st mesocycle than in the 6th. %HRmax values were also greater (3.3%, 1.3-5.4%) in the 3rd mesocycle than in the first. Furthermore, training load was lower on the day before match (MD-1) than 2 (MD-2) to 5 (MD-5) d before a match, although no difference was apparent between these latter time points. Conclusions: The authors provide the 1st report of seasonal training load in elite soccer players and observed that periodization of training load was typically confined to MD-1 (regardless of mesocycle), whereas no differences were apparent during MD-2 to MD-5. Future studies should evaluate whether this loading and periodization are facilitative of optimal training adaptations and match-day performance